Optimasi Proses Produksi Biskuit Tinggi Protein Berbasis Soy Protein Concentrate (SPC) - Zahidah Khairina; Mohamad Djali; Robi Andoyo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Most biscuits contain an unbalanced macronutrient composition, high in carbohydrates and fat but low in protein. Additional protein sources can be incorporated to enhance their protein content. Soy protein concentrate is a highly digestible plant-based protein source. However, adding high amounts of protein can result in a harder biscuit texture, which may reduce consumer acceptance. The increased hardness caused by the natural properties of protein can be modified by altering its structure through preheating treatment. This study aimed to determine the optimal formulation based on the protein concentration and preheating temperature of soy protein concentrate to produce high-protein biscuits with good acceptability. Optimization was performed using response surface methodology (RSM) with a central composite design (CCD), evaluating biscuit hardness, stiffness, porosity, and fractal dimension. According to the RSM design, 13 experimental runs with 5 center points were conducted using Design Expert 13 software. Based on biscuit attributes such as hardness, stiffness, fractal dimension, and porosity, the optimal formulation was achieved with a protein content of 12.614% and a preheating treatment at 72.93 °C.